SCIENTIFIC PICTURE OF THE WORLD AS A MEANS FOR INTERPRETATION AND SYSTEMATIZATION OF SPECIAL KNOWLEDGE - Гінзбург, М. Д. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article proposed a comprehensive interdisciplinary approach to cognition of the real world and to language fixation of the special knowledge. This approach allows combining the results of many sciences and can be a methodological basis for further case studies, in particular process description in the languages for special purpose.